DIALECTICAL RELATIONSHIP BETWEEN CULTURE AND THE CONCEPT OF SOCIAL JUSTICE (Conferencea, 2025)
The dialectical relationship between culture and the concept of social justice is a critical area of inquiry in contemporary social theory. This article explores how cultural frameworks shape, and are shaped by, notions of social justice. By examining theoretical paradigms, methodological approaches, and practical applications, the paper illustrates the interplay between cultural values, norms, and practices and the pursuit of equitable social systems. Case studies and examples highlight the bidirectional influence of culture and social justice, emphasizing the importance of this relationship in policy-making, education, and community development.